ANALISIS NILAI PENDIDIKAN KARAKTER DALAM KEBUDAYAAN LOKAL MOTIF BATIK JETIS DI SIDOARJO - izah nurfitriyah silvi (PRODI PGSD STKIP PGRI SIDOARJO, 2022)
This research is important because it aims to strengthen character values ​​through local wisdom in Sidoarjo, namely the meaning and symbolic value of Sidoarjo jetis batik motifs which can be integrated into social life. This type of research is a mix methods research by first analyzing qualitative research, namely by analyzing the meaning and value of the jetis batik motif. There are 3 informants in this research, namely batik owners, batik workers and batik consumers. After analyzing that (a) There is a symbolic meaning in the jetis batik motif, it is proven by the presence of several motifs that correspond to the 18 character values, namely the sugarcane garden, spinach flower, sekar jagad, utah rice, sekardangan, milkfish and fan motifs. (b) There is an integration of symbolic meanings and values ​​in jetis batik motifs with character education for the surrounding community by identifying economic activities and their relationships with various fields of work as well as social and cultural life in the surrounding environment up to the province.